Rare decay K+ →π+ ν ν̄ at the next-to-next-to-leading order m QCD - Buras, A; Gorbahn, M; Haisch, U; Nierste, U (2005)
We calculate the charm quark contribution to the rare decay K+ →π+ ν ν̄ in the next-to-next-to-leading order of QCD. This new contribution reduces the theoretical uncertainty in the relevant parameter P c from ± 10.1% down to ± 2.4%, corresponding to scale uncertainties of ± 1.3%, ± 1.0%, ± 0.006, and ± 1.2° in B (K+ →π+ ν ν̄ and in |Vtd|, sin2β extracted from the K →π+ ν ν̄ system. The error Pc0. 37±0.04 is now fully dominated by the current uncertainty of ±3.8% in the charm quark mass mc. We find B (K+ →π+ ν ν̄)=(8.0±1.1)×10-11, where the quoted error stems almost entirely from the present uncertainties in mc and the Cabibbo-Kobayashi-Maskawa elements. © 2005 The American Physical Society.